Women’s Health Decision-Making: Evidence From 2017 Demographic and Health Surveys Data - Agustina Saputri; Theresia Theresia; Deby Kristiani Uligraff; Novita Sari Barus (SEHATI: Jurnal Kesehatan, 2025)
Women’s decision-making is an important element in preventing treatment delays. Indonesian women traditionally always depend on their family to decide on treatment. Therefore, this study aims to find out who makes decisions about health problems and analyze the factors associated with the characteristics of women who act as decision-makers in their families when facing health problems.  This study used the individual subset data on married women from the 2017 Indonesia Demographic and Health Survey, which included women of reproductive age (15-49 years). Descriptive statistical analysis will be used in this study. Results: Women’s health decision-making had a significant relationship with all demographic variables. Factors that have influenced women to decide about their health issues were higher educational level (p-value=0.000), have been exposed to the media (p-value=0.047), used the internet (p-value=0.000), had a bank account (p-value=0.000), employed (p-value=0.000), and lived in urban areas (p-value=0.000). Based on this result highly educated women are 2.5 times more likely to be health-related decision-makers.  Conclusion: Highly educated women increased the authority of women to be decision-makers in their families, especially in health issues. By having a high education, women can determine the actions taken for manage health of themselves and their families